2023
DOI: 10.1136/jmg-2023-109196
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pathogenic variants in breast cancer susceptibility genes in bilateral breast cancer

Abstract: PurposeTo investigate the frequency of germline pathogenic variants (PVs) in women with bilateral breast cancer.MethodsWe undertookBRCA1/2andCHEK2c.1100delC molecular analysis in 764 samples and a multigene panel in 156. Detection rates were assessed by age at first primary, Manchester Score, and breast pathology. Oestrogen receptor (ER) status of the contralateral versus first breast cancer was compared on 1081 patients with breast cancer withBRCA1/BRCA2PVs.Results764 women with bilateral breast cancer have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Bilateral breast cancer has been identified as an independent predictor for BRCA1/2 mutation. Various studies have shown that the detection rate of BRCA1/2 gene mutations can be high in patients with bilateral breast cancer [ 50 , 51 ]. Yuntao Xie et al recently developed a nomogram, BRCA -CRisk, to accurately predict the risk of contralateral breast cancer in patients with BRCA1/2 mutations [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral breast cancer has been identified as an independent predictor for BRCA1/2 mutation. Various studies have shown that the detection rate of BRCA1/2 gene mutations can be high in patients with bilateral breast cancer [ 50 , 51 ]. Yuntao Xie et al recently developed a nomogram, BRCA -CRisk, to accurately predict the risk of contralateral breast cancer in patients with BRCA1/2 mutations [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most common genetic tests in the diagnosis of breast cancer are the following: First, predictive genetic tests look for inherited mutations in genes that increase the risk of breast cancer, such as BRCA1, BRCA2, and TP53 [ 21 ]. These tests identify people with a high chance of developing breast cancer in the future.…”
Section: Using Genetic Analysis Of Tissue Samples To Identify Breast ...mentioning
confidence: 99%
“…A total of nine studies (22)(23)(24)(25)(26)(27)(28)(29)(30) presented frequencies of germline variants that allowed the following comparisons: HR-HER2+ versus TNBC (Supplementary Figure 5), HR-HER2+ versus HR+HER2-(Supplementary Figure 6), HR+HER2+ versus TNBC (Supplementary Figure 7), HR+HER2+ versus HR+HER2-(Supplementary Figure 8), and HR+HER2+ versus HR-HER2+ (Supplementary Figure 9). Moreover, eleven studies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) allowed the comparison of HR+HER2versus TNBC (Supplementary Figure 10). For each comparison, genes were included when a variant was reported in at least two studies.…”
Section: Meta-analysis Of Germline Variants Among Bc Subtypesmentioning
confidence: 99%